If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 9 = 13x + -27 Reorder the terms: 9 + 7x = 13x + -27 Reorder the terms: 9 + 7x = -27 + 13x Solving 9 + 7x = -27 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 9 + 7x + -13x = -27 + 13x + -13x Combine like terms: 7x + -13x = -6x 9 + -6x = -27 + 13x + -13x Combine like terms: 13x + -13x = 0 9 + -6x = -27 + 0 9 + -6x = -27 Add '-9' to each side of the equation. 9 + -9 + -6x = -27 + -9 Combine like terms: 9 + -9 = 0 0 + -6x = -27 + -9 -6x = -27 + -9 Combine like terms: -27 + -9 = -36 -6x = -36 Divide each side by '-6'. x = 6 Simplifying x = 6
| n(n-1)=132 | | 1/3v-3/2=-3/5 | | n(n-1)=32 | | y^2-26y+160=0 | | x+44=4x+20 | | C=250+40d | | 4x-14=x+13 | | x-11=4x+16 | | 5-(6+9x)=(4x-1) | | 7.13=2(3.14)r | | 8x+7-3x=5+5x+2 | | 2x-8y-9x+5y= | | -8(-3s-6+8m)= | | X^2-4=45 | | x(x-4)-2=43 | | 77.4(0.681)= | | X+60=35 | | (2+v)(2v+3)=0 | | 3x(12x-5)-6x(6x-5)=0 | | 4x^3-9x^2+7x=2.5 | | 6x-17=2x+15 | | (√48)^(1/2) | | y=5-2n | | 8x-5y=2132 | | 2x+3(2x-5)=6 | | 13+3x=-91-10x | | 2x+15=4x+11 | | 34m-5-1/2m=1 | | 24-4x=9-7x | | X-(7x-8)= | | 8x-y=32 | | 5/6=1/x |